Poligami Tanpa Persetujuan Istri: Implikasi Hukum, Dampak Psikologis dan Analisis Kritis terhadap Pendapat Publik Figur - Rema Syelvita; Utami Niki Kusaini (University Of Bengkulu Law Journal, 2025)
Polygamy conducted without the consent of the first wife remains a complex legal issue within the framework of Indonesian national law, despite Islamic law permitting the practice under certain conditions. This article aims to analyze the legal implications of polygamy without the wife's consent based on Islamic legal principles and relevant Indonesian legislation. The study employs a normative juridical method, using a statutory and case-based approach by examining relevant court decisions. The findings indicate that such polygamous practices may result in serious legal consequences, including potential violations of justice principles and the protection of women's rights within marriage. Moreover, this practice has the potential to create legal uncertainty and lead to injustice for the affected wives and children.